Study on construction waste and debris management in Majlis Perbandaran Subang Jaya (MPSJ) / Abdur Razak Alimin - Alimin, Abdur Razak (Faculty Architecture, Planninng and Surveying, 2014)
Malaysia construction industry nowadays generates a large quantity of construction waste on new development project, demolition and renovation works. Construction debris and waste can be defined as a mixture of surplus materials arising from any excavation, civil or building construction, site clearance demolition activities, road works, and building works. The disposal of construction and debris waste at landfills has caused major environmental concerns and government sources indicate that there is an acute shortage of landfill space ion Malaysia. The aims of this study are to give background management and implementation of construction and debris waste problems in Malaysia and propose a practical guidance to building professional on how to manage and minimise construction waste and debris on MPSJ and contractor perspective in current trend of construction industry. Construction site waste management is not the major issues in construction site nowadays. But, with the new development of town and country, it probably will increase time to time and it is also effect directly into environmental issues. Further developments are recommended to develop a scientific methodology to do inadequate and advance planning on construction and debris waste. Furthermore, more practical support is required to enforce the implementation of construction & debris waste management scheme and plan in the construction and building field. It is also recommended to extend further research on to developing programmes on long term step in order to create and increasing level of awareness to construction waste and debris management Malaysia construction industry